Savings and financial sector development: Panel cointegration evidence from Africa - Roger Kelly; George Mavrotas (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2003)
The paper uses different measures of financial sector development for a dynamic heterogeneous panel of 17 African countries to examine the impact of financial sector development on private savings. An innovative econometric methodology is also employed related to a series of cointegration tests within a panel. This is an important contribution since traditional panel data analysis adopted in previous studies suffers from serious heterogeneity bias problems. The empirical results obtained vary considerably among countries in the panel, thus highlighting the importance of using different measures of financial sector development rather than a single indicator. The evidence is rather inconclusive, although in most of the countries in the sample a positive relationship between financial sector development and private savings seems to hold. The empirical analysis also suggests that a change in government savings is offset by an opposite change in private savings in most of the countries in the panel, thus confirming the Ricardian equivalence hypothesis. Liquidity constraints do not seem to play a vital role in most of the African countries in the group, since the relevant coefficient is negative and significant in only a small group of countries.
Keywords: E21; E44; C22; 330; financial sector development; private savings; panel cointegration tests; Africa; Finanzsektor; Sparen; Afrika